2011
DOI: 10.5424/sjar/20110902-124-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ethylene production by ten Mediterranean carnation cultivars and their response to ethylene exposure

Abstract: Vase life is one of the most important characters of postharvest cut flower quality. The onset of ethylene production and the amount of ethylene produced by flowers vary with the carnation cultivar, and thus influence their vase life. In the present study, differences in ethylene production and the response to exogenous ethylene among carnation cultivars were evaluated. Ten different cultivars: 'Baltico', 'Domingo', 'Exotica', 'Famosa', 'Kiro', 'Madame Augier', 'Master', 'Mundo', Pilar' and 'Reina' were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(13 reference statements)
1
1
0
1
Order By: Relevance
“…Our results here and in previous studies indicate that variation in flower vase life is not due to differences in ethylene sensitivity, but to differences in ethylene production. Similar results were reported by Ebrahimzadeh et al (2011) using ten Mediterranean carnation cultivars.…”
Section: Discussionsupporting
confidence: 77%
“…Our results here and in previous studies indicate that variation in flower vase life is not due to differences in ethylene sensitivity, but to differences in ethylene production. Similar results were reported by Ebrahimzadeh et al (2011) using ten Mediterranean carnation cultivars.…”
Section: Discussionsupporting
confidence: 77%
“…However, the response to exogenous ethylene varied between the two species. In agreement with these results, variations in the sensitivity of species or cultivars have been reported in important cut flowers such as orchids [15], carnations [18,29,31], tulips [17], roses [21,32], petunias [33], and dahlias [23]. These findings suggested that the extent of ethylene production and its effect on cut flowers vary widely according to species or cultivars, indicating that sensitivity varies among different cut flowers.…”
Section: Effects Of Exogenous Ethylene On the Appearance And Vase Liv...supporting
confidence: 73%
“…Some long-life cultivars, such as 'Chinera' and 'Epomeo' , have lower ethylene sensitivities than the normal Sim-type cultivar 'White Sim' (Wu et al 1991). However, Ebrahimzadeh et al (2011) observed that some long vase life cultivars show high ethylene responsiveness and, in contrast, cultivars with a short vase life show low responsiveness. In this regard, Onozaki et al (2004) reported that Mediterranean carnation cultivars show more variation in ethylene production and sensitivity than Standard Sim-type cultivars.…”
mentioning
confidence: 94%